Functional genetic variation in the Rev-Erbα pathway and lithium response in the treatment of bipolar disorder - McCarthy, Michael J. (2011)
Bipolar disorder (BD) is characterized by disruptions in circadian rhythms such as sleep and daily activity that often normalize after lithium treatment in responsive patients. Since lithium is known to interact with the circadian clock, we hypothesized that variation in circadian “clock genes” would be associated with lithium response in BD. We determined genotype for 16 variants in 7 circadian clock genes, and conducted a candidate gene association study of these in 282 Caucasian BD patients who were previously treated with lithium. We found that a variant in the promoter of NR1D1 encoding Rev-Erbα (rs2071427) and a second variant in CRY1 (rs8192440) were nominally associated with good treatment response. Previous studies have shown that lithium regulates Rev-Erbα protein stability by inhibiting GSK3β. We found that GSK3β genotype was also suggestive of a lithium response association, but not statistically significant. However, when GSK3β and NR1D1 genotypes were considered together, they predicted lithium response robustly and additively in proportion to the number of response-associated alleles. Using lymphoblastoid cell lines from BD patients, we found that both the NR1D1 and GSK3β variants are associated with functional differences in gene expression. Our findings support a role for Rev-Erbα in the therapeutic mechanism of lithium and suggest that the interaction between Rev-Erbα and GSK3β may warrant further study.